Optimisasi Proses Pengupasan dan Pengirisan Bawang Merah dengan Teknologi Terbaru - Zainal Fanani, Nurul; Baihaqi, Imam; Saiful Rizal, Ahmad; Surahman, Abi; Setiawan Aji P, Ugi (P3M Politeknik Negeri Cilacap, 2025)
Shallots (Allium ascalonicum L.) are essential tuber crops in the food industry, enhancing the aroma and flavour of various dishes. Manual peeling and slicing of shallots are time-consuming and can cause eye irritation. This study aims to develop and test an integrated shallot peeling and slicing machine to improve processing efficiency and reduce discomfort. The machine used in this study has a capacity of 3 kg. Peeling tests were conducted with shallots weighing 1 kg, 2 kg, and 3 kg, recording the time needed for each weight. Slicing tests were conducted with shallots weighing 0,5 kg, 1 kg, 1,5 kg, and 2 kg, measuring the thickness of the slices produced. The results show that the machine takes approximately 6 minutes to peel 1 kg of shallots and 4 minutes for 2 kg and 3 kg, demonstrating 30 times the efficiency of manual peeling. Slicing 0,5 kg of shallots resulted in 0,5 mm thick slices, while for 1 kg and 2 kg, the slice thickness was consistently 0,4 mm. For 1,5 kg, the slice thickness was 0,7 mm, with the machine's slicing performance improving approximately 3 times compared to manual methods. This study concludes that the integrated shallot peeling and slicing machine effectively enhances the efficiency and accuracy of shallot processing, making it viable for implementation in the food industry.